ChemInform Abstract: Synthesis of Highly Functionalized Tri‐ and Tetrasubstituted Alkenes via Pd‐Catalyzed 1, 2‐Hydrovinylation of Terminal 1, 3‐Dienes. Issue 26 (June 2015) - Saini, Vaneet; O'Dair, Mark; Sigman, Matthew S.
Abstract Either enol nonaflates or triflates are used for the procedure and a broad spectrum of stereodefined complex target compounds is available under conditions A) or B).